2021
DOI: 10.3390/f12111437
|View full text |Cite
|
Sign up to set email alerts
|

Synanthropic Process Evaluation (with Factors Affecting Propensity to Parasitism) and Host Range within the Genus Ganoderma in Central Europe

Abstract: Ganoderma P. Karst. is a genus of wood decaying fungi with complicated taxonomy due to morphological variability of their basidiomata. Although a wide range of host plants is assumed for the genus as a whole, there is a need for revision of the host specificity of individual species. Based on revision of mycological collections across the Czech Republic we analyzed the ecological trends of six European species, including host preferences and propensity to parasitism. Individual Ganoderma species were sampled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…are predominantly found in the vicinity of tree stumps and roots, and this genus is known as one of the most prevalent plant pathogens. [42][43][44][45] Species within this genus are categorized as white-rot fungi and possess enzymes capable of degrading lignin and cellulose. These enzymatic properties enable Ganoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…are predominantly found in the vicinity of tree stumps and roots, and this genus is known as one of the most prevalent plant pathogens. [42][43][44][45] Species within this genus are categorized as white-rot fungi and possess enzymes capable of degrading lignin and cellulose. These enzymatic properties enable Ganoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…In the United States, G. appnalatum, G. boninense, the G. lucidum complex, G. sessile, and G. zanatum are pathogens in landscape trees(Kües et al, 2015b;Kunta et al, 2010;Loyd, Linder, et al, 2018) The literature has reported that Ganoderma spp. are mainly found near the stumps and roots of trees and that this genus is one of the most common plant pathogens (Grinn-Gofroń et al, 2021;Loyd, Linder, et al, 2018;Náplavová et al, 2021;Sadyś et al, 2014). Species in this genus are white-rot fungi and possess lignin-and cellulose-degrading enzymes that allow Ganoderma spp.…”
mentioning
confidence: 99%